Pengaruh Periklanan (Advertising) dan Harga Terhadap Minat Pembeli di Elshinta Swalayan Sukaraja - Rini Ramdiani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the simultaneous and partial effects of advertising and price on consumer purchase intention at Elshinta Swalayan Sukaraja. The research employed a quantitative method with a survey approach to collect empirical data from respondents. The sampling technique used was incidental sampling, with a total of 100 consumers who shopped at Elshinta Swalayan Sukaraja. Data were collected through questionnaires and analyzed using multiple linear regression to determine the relationships and effects among the studied variables. The results revealed that advertising and price simultaneously have a significant influence on consumer purchase intention. Partially, advertising has a significant effect on increasing purchase intention through the delivery of persuasive and attractive promotional messages. Meanwhile, the price variable also shows a positive influence, indicating that competitive pricing can strengthen consumers’ purchase decisions. Therefore, this study highlights the importance of integrating promotional strategies and pricing policies to enhance consumer purchase intention and improve the retail store’s competitiveness in the local market.